2010
DOI: 10.1016/j.schres.2010.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological prodromal signs of schizophrenic relapse: A pilot study

Abstract: Do physiological changes occur shortly prior to psychotic relapse in schizophrenia outpatients? We addressed this question in a group of schizophrenia outpatients by measuring changes in symptoms and changes in activation of the sympathetic nervous system, as indexed by changes in skin conductance level (SCL), on a biweekly basis for between one and two years. All six outpatients exhibited heightened SCL within two weeks prior to relapse or exacerbation, compared to SCL proceeding continued remission. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…For example, comparisons of diagnosed schizophrenia patients with controls do not show a diagnostic group difference in mean skin conductance level [20][21]. However, a recent study of skin conductance levels in a sample of patients diagnosed with schizophrenia demonstrated that, although levels of skin conductance differed greatly among participants, all manifested a significant increase in skin conductance levels prior to relapse [22]. These results highlight the importance of within-subjects designs for elucidating the impact of stress in psychosis.…”
Section: Psychosocial Stress and Schizophreniamentioning
confidence: 96%
“…For example, comparisons of diagnosed schizophrenia patients with controls do not show a diagnostic group difference in mean skin conductance level [20][21]. However, a recent study of skin conductance levels in a sample of patients diagnosed with schizophrenia demonstrated that, although levels of skin conductance differed greatly among participants, all manifested a significant increase in skin conductance levels prior to relapse [22]. These results highlight the importance of within-subjects designs for elucidating the impact of stress in psychosis.…”
Section: Psychosocial Stress and Schizophreniamentioning
confidence: 96%
“…Interestingly, in animal models, chronic stress such as social isolation or movement restriction may alter the synaptic connectivity at the level of PFC and hippocampus [7] [34]- [37]. For all these reasons, exposure to stress may be a key factor in the precipitation of schizophrenic psychosis in adolescence and in the subsequent exacerbation of its symptoms [38]- [41], suggesting that the environment can and does interact with an already vulnerable circuitry to aggravate cortical deterioration.…”
Section: Prefrontal Cortex Neuropathology In Schizophreniamentioning
confidence: 99%
“…This suggests that changes in an individual's 'state' must contribute to their hallucination proneness. There is substantial evidence (e.g., Dawson, Nuechterlein, Schell, Gitlin, & Ventura, 1994;Dawson et al, 2010;Delespaul, deVries, & van Os, 2002;Lukoff, Snyder, Ventura, & Nuechterlein, 1984) that psychological stress has a 'state effect' on hallucination proneness in clinical populations, such that periods of stress trigger individual occurrences of these symptoms in those vulnerable to them (Slade, 1972). Indeed psychological stress appears to have a similar effect on non-psychotic auditory hallucinations (Johns, Hemsley, & Kuipers, 2002).…”
Section: Stress and Hallucinationsmentioning
confidence: 99%